Mediating Role of Job Satisfaction on the Relationship between Managerial Incentives and Academic Staff Performance of Selected Federal Colleges of Education in Northern Nigeria - Marcus Garvey Orji; Enobun-Nwidi Patience Enyiamaka (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2022)
Inadequate managerial incentive is one of the major causes of poor performance by academic staff in higher institutions. The current study examined the mediating role of job satisfaction on the relationship between managerial incentives and academic staff performance in Federal Colleges of Education in Northern Nigeria. The study employed descriptive survey research design. Population of the study was 1,967 academic staff in the selected Federal Colleges of Education in Northern Nigeria. The sample size of the study was 433 respondents selected from the population. Closed-ended structured questionnaire was used to source for primary data. The copies of questionnaire were issued by hand. Cronbach’s Alpha and Composite Reliability Coefficients were used to measure the reliability of instrument. Data was processed using Partial Least Square Structural Equation Modeling (PLS-SEM). The findings showed that recognition, work environment, training and job satisfaction have positive significant effects on academic staff performance. The study revealed that job satisfaction mediated the relationship between recognition and academic staff performance. The study also found that job satisfaction mediated the relationship between work environment and academic staff performance. But job satisfaction did not mediate the relationship between training and academic staff performance. The implication of the findings of the study is that the management of Federal Colleges of Education will benefit by providing adequate and suitable managerial incentives to academic staff that deserve and desire them to enhance their job satisfaction since satisfied academic staff perform better and contribute to the total success of the institution. The study therefore, recommended that the management of the selected Federal Colleges of Education should continue to provide more recognition, comfortable work environment and provide adequate training to boost the academic staff morale and their level of satisfaction, which in turn results to optimum performance.